(untitled) (The International Journal for Scientific Research, 2025)
For any commutative ring with unity R, a new ring can be defined called the ring of dual numbers of the ring R, denoted by R[α]. In this paper we obtain a characterization of unit and zero-divisor elements in the ring of dual numbers of the ring of integers modulo n, Zn[α].